Integrating Brain-Writing and Small Group Discussion to Enhance Students’ Writing Ability in Descriptive Text - Elbalqis, Putri; Yufrizal, Hery (Universitas Islam Negeri Raden Intan Lampung, 2023)
The use of a technique in the process of teaching writing as a complex skill has a crucial role. This research, the integration of the two techniques; brain-writing and small group discussion was applied in teaching writing descriptive text. The objectives of the research were to find out (1) a significant difference of students’ writing ability before and after being taught by using the integration the two techniques, (2) the aspect of writing which is affected the most by using the integration of the two techniques, (3) the students’ perception towards the implementation of the integration of the two techniques. In the context of methodology, the samples involved were 24 students in SMP Insan Mandiri Bandar Lampung. The data were collected by using pre and post-test of writing and perception questionnaire. The data were analyzed by using paired-sample t-test. The results showed the students’ writing achievement increased from 66.08 to 79.14. The p value is lower than 0.05, meaning that there is a significant difference of students’ writing ability between pretest and posttest. As for writing aspects, the most affected one was content. The students’ perception about the implementation of technique showed a positive result. Thus, the integration of the two techniques is effective to help students to generate and elaborate the ideas into a good descriptive text.